Animal spirits and the business cycle: Empirical evidence from moment matching - Tae-Seok Jang; Stephen Sacht (Kiel University, Department of Economics, 2014)
In this paper we empirically examine a hybrid New-Keynesian model with heterogeneous bounded rational agents who may adopt an optimistic or pessimistic attitude - so called animal spirits - towards future movements of the output and inflation gap. The model is estimated via the simulated method of moments using Euro Area data from 1975Q1 to 2009Q4. In addition, we compare its empirical performance to the standard model with rational expectations. Our empirical results show that the model-generated auto- and cross-covariances of the output gap, the inflation gap and the nominal interest gap can provide a good approximation of the empirical second moments. The result is mainly driven by a high degree of persistence in the output and inflation gap due to the impact of animal spirits on economic activity. Furthermore, over the whole time interval the agents had expected moderate deviations of the future output gap from its steady state value.
Keywords: C53; D83; E12; E32; 330; Animal Spirits; Bounded Rationality; New-Keynesian Model; Simulated Method of Moments